1986
DOI: 10.1093/ajcn/43.1.136
|View full text |Cite
|
Sign up to set email alerts
|

Influence of long-term diet modification on platelet function and composition in Moselle farmers

Abstract: Platelet function and composition, lipemia, and dietary habits were evaluated yearly in 98 male farmers from Moselle (East of France) before and after decreasing, in half of them, dietary saturated fats from 16.2% to 9.9% of calories (P/S from 0.32 to 0.97). One year after these dietary changes, cholesterol and triglycerides decreased by approximately 10%, platelet aggregation to thrombin by 81%, and their clotting activity by 30%. However, ADP aggregation was enhanced by 54%. At 2 yr the P/S was decreased to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(50 citation statements)
references
References 36 publications
7
42
1
Order By: Relevance
“…Based simply on the relationship with total serum cholesterol, one could conclude that maximizing the intake of polyunsaturated fat would be desirable, and some guidelines suggest that intake be increased to 10% of energy (compared with US averages of about 3% in the 1950s and 6 or 7% at present) with a P ⁄ S ratio of 1.0 [57]. Using platelet aggregability rather than serum cholesterol to evaluate the effect of diet, Renaud and colleagues [58] have suggested that a dietary P ⁄ S ratio of 0.6 to 0.8 may be superior to a ratio of 1.0. Within the Nurses' Health Study, intakes up to about 8% of energy could be studied and the dose-response relation appeared to be linearly inverse with no evidence of a plateau [59].…”
Section: Further Aspects Of Dietary Fats and Chdmentioning
confidence: 99%
“…Based simply on the relationship with total serum cholesterol, one could conclude that maximizing the intake of polyunsaturated fat would be desirable, and some guidelines suggest that intake be increased to 10% of energy (compared with US averages of about 3% in the 1950s and 6 or 7% at present) with a P ⁄ S ratio of 1.0 [57]. Using platelet aggregability rather than serum cholesterol to evaluate the effect of diet, Renaud and colleagues [58] have suggested that a dietary P ⁄ S ratio of 0.6 to 0.8 may be superior to a ratio of 1.0. Within the Nurses' Health Study, intakes up to about 8% of energy could be studied and the dose-response relation appeared to be linearly inverse with no evidence of a plateau [59].…”
Section: Further Aspects Of Dietary Fats and Chdmentioning
confidence: 99%
“…A third possibility is that populations with a low fat intake have less body fat 57 -58 ; this would lower coronary risk by itself and would also counteract the HDL-cholesterol lowering and reinforce the LDL cholesterol-lowering effects of a low-fat, high-carbohydrate diet. Also, effects of diet on other risk factors for coronary heart disease such as blood pressure, 59 platelet function, 60 and LDL oxidizability 40 -61 are important. Unfortunately, the extent of these effects in humans is not well defined.…”
Section: Predicted Changes In Risk For Coronary Heart Diseasementioning
confidence: 99%
“…It is now recognized that dietary LA favors oxidative modification of LDL cholesterol (65,66), and increases platelet response to aggregation (67). In contrast, ALA intake is associated with inhibitory effects on the clotting activity of platelets, on their response to thrombin (68,69), and on the regulation of AA metabolism (70). In clinical studies, ALA contributed to lowering of blood pressure (71).…”
Section: Aspects Of Dietmentioning
confidence: 99%